CONTRIBUTION A LA CONNAISSANCE DE L’ETAT ACTUEL DE LA FAUNE BENTHIQUE DE L’ECOSYSTEME ESTUARIEN DE L’EMBOUCHURE DE LA MOULOUYA (MAROC) - Darif, Hajar; Hassouni, Taoufik; Belghyti, Driss; El Kharrim, Khadija; Chiahou, Brahim; El Madhi, Youssef; El Halouani, Hassan (European Scientific Journal, ESJ, 2015)
Moulouya is the largest river flowing into the mediterranean. A study of the current state of the benthic fish fauna of the mouth of the river was conducted between january 2014 and may 2014. The results were used to inventory 47 species divided into 04 classes. Mollusks are the most numerous, with 26 species.Crustaceans representing 33.4% of the population collected. Atyaephyradesmarestii found is the most abundant species (69,4%).This study aims at the realization of a recent taxonomic inventory (2014) wildlife estuarine ecosystem of the mouth of the moulouya (morocco). Indeed four systematic groups and 933 individuals were surveyed.